《回味》= After taste - Lau, Chong Wai (2016)
回味 huí wèi (After Taste) is a narrative short film by 3ple Productions (众製作 zhòng zhì zuò). The team is made up of three undergraduates – Lau Chong Wai, Ng Yihui, Rebecca and Sim Yu Ling. The short film took approximately a year to complete, under the supervision of Mr. Daniel Heng. A primarily Mandarin film sprinkled with English and Cantonese, After Taste reminisces about how growing up used to be much simpler without the intervention of social media; mobile technology was only at its beginning stages, and dual-income families were becoming a norm. Through the narrative, the film explores the sentimentality of homecooked food and the potential of relationships beyond familial ties.